Cranio-cerebral injuries in road accidents: characteristics and clinical process - Pawłowski, Witold; Goniewicz, Krzysztof; Goniewicz, Mariusz; Czerski, Robert (Journal of Education, Health and Sport, 2018)
The constant progress of civilization involves the mechanization of daily life, including in particular the use of motor vehicles, mainly cars and all sorts of two-wheelers. The rapid growth of the automotive industry in the world has brought a huge increase in traumatism. The aim of the study was to characterize cranio-cerebral and to provide a substrate for further study provided within the subject. Injuries arising as a result of rotational forces in protected road users usually cause minimal damage to the exterior of very serious internal injuries. During the evaluation of the injured at the scene of the injury victims should receive occiput red color in the medical segregation